EFFECTS OF COVID-19 PANDEMIC ON TRANSPORTATION, DISTRIBUTION AND MARKETING OF AGRICULTURAL PRODUCTS IN NASARAWA STATE, NIGERIA - Ajiboye, Araoye Olarinkoye; Tsaku, Dan .O; Alhassan Elijah Aina; Oluda Muhammed Eludaiye; Eko- Rapheals Melvin. U; Mujakachi Tapiwa Christopher (Nigerian Journal of Agriculture and Agricultural Technology (NJAAT), 2024)
Nigeria is an agrarian economy with high production of agricultural products. However, the emergence of Covid-19 disease in the country and its spread across the nation as well as the lockdown policies of the Federal and State governments has compounded the socio-economic condition of the people. It is on this premise that this study examines the effects of Covid-19 Pandemic and the lockdown policies of the government on the transportation and distribution of agricultural products in Nasarawa Eggon Local Government of Nasarawa State, Nigeria. The study adopted the survey approach applying simple random techniques with the use of a well-structured questionnaire to collect information on the effects of Covid-19 among farmers, traders and transporters of agricultural products in the study area. Both descriptive and regression statistics were used to achieve the collected data. Results of the study shows that Covid-19 pandemic significantly impacted transportation factors (R2=0.553, F=103.238, p=0.000), distribution factors (R2=0.260, F=17.125, p=0.000), and marketing factors (R2=0.559, F=61.871, p=0.000) of agricultural products in the study area. It is therefore concluded that the Covid-19 pandemic and lockdown policies significantly impacted the transportation and distribution of agriculture in the study area. Therefore, there is an urgent need to curb the menace and for the governments to provide palliative for the people.
Keywords: Agriculture; Covid-19; Distribution; Marketing; Product; Transportation